Determination of rock fracture toughness under creep and fatigue - Celestino, T. B.; Bortolucci, A. A.; Nobrega, C. A. [UNESP] (My University, 1995)
The paper describes the results of stable servo-controlled Brazilian compression tests on granite. The tests have been successfully used for the determination of rock fracture toughness. In the tests described here, after a fracture has been created through approximately one fourth of the diameter length, the load has been reduced, and the specimens have been taken to failure under fatigue or creep. The relationship between crack propagation rate and stress intensity factor during creep was obtained. Rock Mechanics, Daemen & Schultz (eds).